EFFICACY OF ANTENATAL MANAGEMENT IN AYURVEDA DURING 8TH AND 9TH MONTH OF PREGNANCY (AYUSHDHARA, 2021)
Garbhini paricharya is advised for preventing harm to mother and fetus, to attain full fetal maturity and for normal uneventful labour. By keeping this goal in mind the Upakrama of Niruha basti and Anuvasana basti was selected. 100 patients were selected for this study and divided into two groups. In Control Group, there are 50 patients with Standard management (iron+ calcium) with routine diet during pregnancy. In Trial Group, there are 50 patients with Standard management (iron+ calcium) along with Garbhini paricharya.The clinical study was done for evaluation of efficacy of antenatal management in Ayurveda during 8th & 9th month of pregnancy. Bala taila is highly effective to bring about spontaneous labour onset at optimal time. Duration of labour was reduced by Bala siddha taila basti due to its regulation of Prasuti Marut.Maternal and foetal complications during ante natal and post natal period are reduced due to Bala siddha taila Anuvasan basti, Niruha basti and due to high quality nutritive supplementation (Mudga & Masha Yavagu).Maternal as well as fetal weight gain was good due to high quality nutritive supplementation as described in Ayurvedic texts, and it provides optimal nutrition of mother and fetus. The Ayurvedic regimen has promise of providing the optimal and balanced nutrition by using quality ingredients.